Comparative Efficacy and Usefulness of Acebutolol and Diltiazem for the Prevention of Atrial Fibrillation during Perioperative Time in Patients Undergoing Pulmonary Resection - Ciszewski, Pawel; Tyczka, Joanna; Nadolski, Jacek; Roszak, Magdalena; Dyszkiewicz, Wojciech (The Thoracic and Cardiovascular Surgeon, 2013)
Background Postthoracic surgery atrial fibrillation (AF) is the most frequently occurring arrhythmia. Strategies for preventing AF have been amply evaluated, but currently there are no clearly defined guidelines for treatment of AF after thoracic surgery.Methods The study was prospective and randomized controlled trial. Acebutolol and diltiazem versus placebo were compared, among 117 patients postpneumonectomy or lobectomy at the Thoracosurgery Clinic, Poznan University of Medical Sciences in Poland. Patients who were enrolled in the study were randomly assigned to one of the three groups: those who received acebutolol (Group 1) or diltiazem (Group 2) and compared with patients without antiarrhythmic drugs (Group 0). Each group consisted of 39 patients. The patients were continuously monitored postoperatively with 24 ECG (Holter monitor) in the intensive care unit.Results In patients receiving acebutolol AF occurred in 5% compared with 23% of patients receiving diltiazem and 20% of patients receiving placebo (difference not statistically significant).Conclusions Acebutolol and diltiazem appear to have been non-effective for the treatment or prevention of AF. Side effects were mild. In comparison to diltiazem, however, acebutolol had a beneficial effect on the circulatory system. Patients who had received acebutolol proved to have had fewer tachycardia episodes and supraventricular ectopy during the postoperative period. It seems that acebutolol can be useful, especially in patients with sympathetic activity dominance.
Keywords: atrial fibrillation; thoracic surgery; arrhythmia; acebutolol; diltiazem